Immovable property tax in the Czech Republic as an instrument of fiscal decentralization - Janoušková, Jana; Sobotovičová, Šárka (Technological and Economic Development of Economy, 2016)
The issue of fiscal decentralization is connected with efforts to build a space for own decision-making in municipalities when raising funds. In the framework of fiscal decentralization, municipalities in the Czech Republic have an opportunity to influence immovable property tax revenues. The aim of the research is to find out the municipalities’ attitude towards the possibility of increasing immovable property tax revenues through a coefficient and how this option is used by municipalities. In the article, there is a description of the immovable property tax development in the Czech Republic on the basis of time series. The research relies on the evaluation of secondary statistical data and on the results of primary research focused on the application of the local coefficient. Municipalities have the option to edit tax components and the amount of tax reflects then the specificities and needs of the community. However, almost 92% of municipalities still postpone the introduction of a local coefficient. The motivation for the introduction of local coefficients was an increase in municipalities’ revenues generally or the need to fund specific projects. On the other hand the empirical research showed that some form of compensation is introduced in 46% of the municipalities. First published online: 23 Nov 2016